If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5y-6y=-y
We move all terms to the left:
5y-6y-(-y)=0
We add all the numbers together, and all the variables
5y-6y-(-1y)=0
We add all the numbers together, and all the variables
-1y-(-1y)=0
We get rid of parentheses
-1y+1y=0
We add all the numbers together, and all the variables
=0
y=0/1
y=0
| 2x=1+4x/3 | | 6-8p=38. | | 5(y-3=30 | | 1/2x^2-11/24x=-1/2 | | 8-4a=16-8a | | 2(0.3r+1)=23=-0.1r | | (-8z+-24)-12=4 | | 161=7(3-4a) | | r²=44 | | 0.4(5x+15)=2.9(x+3) | | 161=7(3−4a) | | 3x2+12x−180=0 | | 5(x-1)3x+10=8x | | 15+6.9n=13+7.1n | | 7-x=-3-6x | | 12-6x=-3x | | 6(5x-7)=6x | | -4(6x-4)=-24x-16 | | 3x+18x=14 | | F(x)=11x-5=45 | | d3–10=–2 | | 0.2n+6=11.8 | | x6+7=21 | | 12+6x=126 | | —1.56=1+x/2 | | -266=14x | | -3s+2s-4s-13=-7 | | 26/7=18/a | | 3(x-4)+2=2(x-1) | | 5x+2x+20=30 | | 10-(-2)=m=6-16-(-4) | | 26/7=18a |